The impact of telework on absenteeism, presenteeism, and return to work among workers with health conditions: a scoping review - Ducas, Julien; Daneau, Catherine; Bouqartacha, Salma; Lecours, Alexandra; Abboud, Jacques; Marchand, Andrée-Anne; Descarreaux, Martin (Frontiers in Public Health, 2025)
IntroductionTelework has become increasingly prominent as a flexible work arrangement, particularly since the COVID-19 pandemic. For workers managing health conditions, it may support continued employment by influencing key work-related phenomena such as absenteeism, presenteeism and return to work (RTW) process. However, current evidence on the impact of telework on the work-related outcome to manage health condition in the workplace remains limited and fragmented.ObjectiveThis scoping review aimed to map the existing literature on the impact of telework on absenteeism, presenteeism, and RTW outcomes among adult workers with health conditions.MethodsIncluded studies were either qualitative, quantitative, or mixed methods, published in English or French, including adults with any physical or psychological health conditions. At least one outcome domain (absenteeism, presenteeism, or RTW) was required. Eight databases were searched from inception to May 2025: Medline, CINAHL, APA PsycINFO, Academic Search Complete, Business Source Complete, Scopus, Sociological Abstracts, and ABI/INFORM Global. Data extraction focused on study design, objectives, variables/definitions, sample size, health status, demographic characteristics, individual characteristics, organizational factors and results. Data were synthesized by the outcome domain (absenteeism, presenteeism, RTW) and stratified by study type (quantitative vs. qualitative).ResultsFrom 4,093 records, 21 studies were included. The majority of studies suggest that telework contributes to reduced absenteeism by increasing work flexibility. Telework is also consistently associated with facilitating RTW, particularly following surgery or in the context of chronic illness, by supporting work reintegration and shortening the duration of sick leave. In contrast, findings on presenteeism are conflicting: some studies report that telework increases the likelihood of working while sick, others suggest a decrease, and some report no significant impact or conflicting results. These outcomes appear to be influenced by contextual factors, including health status, demographic variables, individual characteristics, and organizational context.ConclusionTelework appears to offer flexibility that can reduce absenteeism and facilitate RTW. However, its impact on presenteeism is less consistent and may even encourage working while sick if not properly supervised. Future studies should examine which policies most effectively maximize the benefits of telework while minimizing potential drawbacks.